“The Whole World Is Mine”. NOF4’s Graffiti Between Norms, Abnormality, and Processes of Subjectivation - Luigi Lobaccaro (Actes Sémiotiques)
This contribution offers a semiotic analysis of Ferdinando Oreste Nannetti’s (NOF4) graffiti on the wall of the psychiatric hospital in Volterra. These inscriptions are examined as a practice that simultaneously expresses a condition of deviation and establishes a regime of autonomous normativity. The asylum wall–an architectural element of the psychiatric apparatus—serves as the interface where heterogeneous normative orders (medical, institutional, existential) come into tension. The paper investigates these layered forms of normativity by analyzing the institutional status of the work, the space in which it is inscribed, the relationship between the psychiatric “total institution” and its internees, and the specific features of schizophrenic enunciation. It argues that the assemblage of these elements gives rise to a new precarious process of subjectivation.